Self-Designed Ningxin Anshen Formula for Treatment of Post-ischemic Stroke Insomnia: A Randomized Controlled Trial - Dai, Ning; Li, Yuanyuan; Sun, Jing; Li, Feng; Xiong, Hang (Frontiers in Neurology, 2020)
This study aimed to assess the efficacy and safety of self-designed Ningxin Anshen (NXAS) Formula for post-ischemic stroke insomnia of blood-deficient and liver-heat syndrome. Ninety patients were randomized into NXAS group, Placebo group and Zopiclone group. Patients in the NXAS group, Placebo group and Zopiclone group were treated with Ningxin Anshen Formula, placebo and zopiclone for 4 weeks, respectively. The scores of the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI) and traditional Chinese Medicine (TCM) Syndromes of self-designed scale and the number of adverse events (AEs) were determined. Results showed that the overall effective rate in the NXAS group and Placebo group was 76.67% and 30.00%, respectively, showing significant difference (P<0.01). There was no marked difference between Zopiclone group (80.00%) and NXAS group. In both NXAS group and Zopiclone group, the scores of PSQI, ISI, and TCM Syndromes of self-designed scale after 4-week treatment were significantly different from those before treatment (P<0.01). After 4-week treatment, the scores of PSQI, ISI, and TCM Syndromes of self-designed score were comparable between NXAS group and Zopiclone group (P>0.05). Only one patient in the NXAS group developed gastrointestinal discomfort, which resolved without treatment discontinuation. In conclusion, self-designed NXAS Formula is effective and safe and has little adverse effect in treating post-stroke insomnia of blood-deficient and liver-heat syndrome.